PEMANFAATAN MINYAK JELANTAH SEBAGAI FOTOKATALIS CARBON NANODOTS UNTUK PENJERNIHAN AIR LIMBAH BATIK - Aan Priyanto; Devin Sidik Prayogi; Nila Fitriya; Jotti Karunawan; Sulhadi Sulhadi; Mahardika Prasetya Aji (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Pollution of batik dye waste on water becomes an environmental problem which requires treatment. Photocatalyst technique using carbon nanodots (C-Dots) from waste frying oil with sunlight irradiation is an effective method to solve the problem. C-Dots from waste frying oil are produced by hydrothermal method at a temperature of 3000C for 150 minutes. C-Dots from waste frying oil used as photocatalyst material in batik waste solution with time variation of sunlight irradiation. The results of the photocatalytic process showed that the solution of batik waste experienced concentration degradation. This was observed from the color change of the solution and based on the analysis of digital image processing showed an increase in intensity value of Black and White with increasing the time of sunlight irradiation in photocatalytic process. The longer the irradiation time of the sun, the clearer the resulting solution, and the increased the intensity of black and white (grayscale) produced. This indicates that the elements contained in the batik waste solution have degraded the concentration so that the particles that can reflect light from the camera are getting less. These results show that C-Dots from waste frying oil have an excellent potential to be developed as water purification photocatalyst material.Keywords: Waste frying oil, Carbon nanodots, Photocatalyst, Waste batik water